Challenges in estimating effective population sizes from metagenome-assembled genomes - Wang, Xiaojun; Feng, Xiaoyuan (Frontiers in Microbiology, 2024)
Effective population size (Ne) plays a critical role in shaping the relative efficiency between natural selection and genetic drift, thereby serving as a cornerstone for understanding microbial ecological dynamics. Direct Ne estimation relies on neutral genetic diversity within closely related genomes, which is, however, often constrained by the culturing difficulties for the vast majority of prokaryotic lineages. Metagenome-assembled genomes (MAGs) offer a high-throughput alternative for genomic data acquisition, yet their accuracy in Ne estimation has not been fully verified. This study examines the Thermococcus genus, comprising 66 isolated strains and 29 MAGs, to evaluate the reliability of MAGs in Ne estimation. Despite the even distribution across the Thermococcus phylogeny and the comparable internal average nucleotide identity (ANI) between isolate populations and MAG populations, our results reveal consistently lower Ne estimates from MAG populations. This trend of underestimation is also observed in various MAG populations across three other bacterial genera. The underrepresentation of genetic variation in MAGs, including loss of allele frequency data and variable genomic segments, likely contributes to the underestimation of Ne. Our findings underscore the necessity for caution when employing MAGs for evolutionary studies, which often depend on high-quality genome assemblies and nucleotide-level diversity.